Analisis Faktor Risiko Kejadian Hipertensi di Wilayah Kota Depok: Analysis of Risk Factors for Hypertension in the Depok City Area - Asri, Intan Puspita; Pitriani Salamah, Nurul; Maryanah Putri, Anna; Putri Nabila E, Shofia; Khairunnisa, Aisyah; Afifah, Faidah; Kusumastuti, Istiana (MPI Press, 2022)
Introduction: Hypertension is a non-communicable disease which is often called